Animal models of fear and anxiety: neurobehavioral descriptions - Mora Gallegos, Andrea (2014)
Animal models of fear and anxiety have been widely used for the comprehension of anxiety disorders in humans, however, it has not been easy to distinguish between both concepts at physiological and behavioral levels. One way to model anxiety disorders is through behavioral tests of anxiety, (such as the elevated plus maze and the open field test), and fear (using the fear conditioning paradigm and active avoidance). Furthermore, animal models are relevant to study the involvement of different brain areas, like the amygdala, hippocampus and prefrontal cortex. In general, fear and anxiety can be considered as normal adaptive responses; however, elevated levels of both might generate detrimental consequences for the individual.